Extent of altered white matter in unilateral and bilateral periventricular white matter lesions in children with unilateral cerebral palsy - Scheck, S.; Fripp, J.; Reid, L.; Pannek, K.; Fiori, S.; Boyd, Roslyn; Rose, S. (Pergamon Press, 2016)
Aims: To investigate the extent of white matter damage in children with unilateral cerebral palsy (UCP) caused by periventricular white matter lesions comparing between unilateral and bilateral lesions; and to investigate a relationship between white matter microstructure and hand function. Methods and procedures: Diffusion MRI images from 46 children with UCP and 18 children with typical development (CTD) were included. Subjects were grouped by side of hemiparesis and unilateral or bilateral lesions. A voxel-wise white matter analysis was performed to identify regions where fractional anisotropy (FA) was significantly different between UCP groups and CTD; and where FA correlated with either dominant or impaired hand function (using Jebsen Taylor Hand Function Test). Outcomes and results: Children with unilateral lesions had reduced FA in the corticospinal tract of the affected hemisphere. Children with bilateral lesions had widespread reduced FA extending into all lobes. In children with left hemiparesis, impaired hand function correlated with FA in the contralateral corticospinal tract. Dominant hand function correlated with FA in the posterior thalamic radiations as well as multiple other regions in both left and right hemiparesis groups. Conclusions and implications: Periventricular white matter lesions consist of focal and diffuse components. Focal lesions may cause direct motor fibre insult resulting in motor impairment. Diffuse white matter injury is heterogeneous, and may contribute to more global dysfunction.What this paper adds. •Focal white matter alterations are observed in the corticospinal tract in UCP with unilateral white matter lesions•Diffuse white matter alterations throughout all cerebral lobes are observed in UCP with bilateral white matter lesions•Fractional anisotropy in the posterior thalamic radiations correlates with dominant hand function.